The Empowering pkk women through socialization of hydroponics using used gallons - Novsatiti, Adi Sadsani Putri; Damayanti, Sabrina Atsila; Nafi’a, Lulu’ Syifa; Fitriahadi, Enny; Hadhad, Nafis Naufal; Wahyuning, Mei Anna Ekha; Althaf, Farrel; Fitriah, Aisyah; Indraswari, Amalia Airin; Rafilla, Nazwa; Wardhono, Bagas Kertiadi (Proceeding International Conference on Health Science and Technology, 2025)
Food security is an important issue in rural communities that still depend on traditional agricultural systems. The hamlet of Plembon Lor faces the challenge of limited rain-fed agricultural land, which results in food insecurity. This community service activity aims to empower PKK mothers through socialization and simple hydroponics practices using used gallons. The implementation method uses a community empowerment approach that actively involves participants in the preparation, socialization, and demonstration stages. The results of the activity show that the majority of participants can understand the concept of hydroponics, are able to make simple installations, and show high motivation to practice independently at home. The main impacts felt were an increase in farming skills, awareness of the importance of family nutrition, and the utilization of household plastic waste. Evaluation of the activity indicated that despite the constraints of limited practice time, participants still gained useful learning experiences. Thus, this activity succeeded in increasing the knowledge, skills, and awareness of PKK mothers in supporting family food security and opening up opportunities for small hydroponic-based businesses